Preparation of Nanofibers of Poly (methyl methacrylate) Composited with Few-Layer-Graphene for Anticorrosion Layer - Thutiyaporn Thiwawong; Korakot Onlaor; Boonthawee Putta; Benchapol Tunhoo (My University, 2021)
An anticorrosion layer is a significant component that prevents the corrosion process in materials. In this work, a nanofiber of poly (methyl methacrylate) composited with few-layer-graphene was prepared as an anticorrosion layer. An electrospinning process was applied to prepare composite nanofiber on a metal substrate at various concentrations of few-layer graphene. The physical properties of the composite nanofiber were investigated with field-emission scanning electron microscope, Raman spectroscopy, and contact angle measurement. The corrosion behavior was tested in an aqueous solution of 3.5% by weight of sodium chloride. It was found that a few-layer graphene concentration of 2 wt% in polymethacrylate showed the optimum anticorrosion on aluminum sheet, as observed on a Tafel graph. Compared with the uncoated metal, the coated aluminum sheet was protected against corrosion with a protection efficiency of 99.33%. The prepared materials prevented the infiltration of water and solution ions into the metal plate.
Keywords: Layer by layer; Poly(N-isopropylacrylamide); Electrospinning; Conducting polymers and applications